Outcomes after endoscopic resection of large laterally spreading lesions of the papilla and conventional ampullary adenomas are equivalent - Klein, Amir; Qi, Zhengyan; Bahin, Farzan F.; Awadie, Halim; Nayyar, Dhruv; Ma, Michael; Voermans, Rogier P.; Williams, Stephen J.; Lee, Eric; Bourke, Michael J. (Endoscopy, 2018)
Background Endoscopic resection of ampullary adenomas is a safe and effective alternative to surgical resection. A subgroup of patients have large laterally spreading lesions of the papilla Vateri (LSL-P), which are frequently managed surgically. Data on endoscopic resection of LSL-P are limited and long-term outcomes are unknown. The aim of this study was to compare the outcomes of endoscopic resection of LSL-P with those of standard ampullary adenomas.Methods A retrospective analysis of a prospectively collected and maintained database was conducted. LSL-P was defined as extension of the lesion ≥ 10 mm from the edge of the ampullary mound. Piecemeal endoscopic mucosal resection of the laterally spreading component was followed by resection of the ampulla. Patient, lesion, and procedural data, as well as results of endoscopic follow-up, were collected.Results 125 lesions were resected. Complete endoscopic resection was achieved in 97.6 % at the index procedure (median lesion size 20 mm, interquartile range [IQR] 13 – 30 mm). Compared with ampullary adenomas, LSL-Ps were significantly larger (median 35 mm vs. 15 mm), contained a higher rate of advanced pathology (38.6 % vs. 18.5 %), and had higher rates of intraprocedural bleeding (50 % vs. 24.7 %) and delayed bleeding (25.0 % vs. 12.3 %). Both groups had similar rates of histologically proven recurrence at first surveillance (16.4 % vs. 17.9 %). Median follow-up for the entire cohort was 18.5 months. For patients with at least two surveillance endoscopies (n = 68; median follow-up 29 months, IQR 18 – 48 months), 95.6 % were clear of disease and considered cured. Conclusions LSL-P can be resected endoscopically with comparable outcomes to standard ampullectomy, albeit with a higher risk of bleeding. Endoscopic treatment should be considered as an alternative to surgical resection, even for large LSL-P.